KEDUDUKAN HUKUM INTERNASIONAL DALAM SISTEM PERUNDANG-UNDANGAN NASIONAL INDONESIA - firdaus firdaus (Fiat Justisia: Jurnal Ilmu Hukum, 2014)
The highest power of articulation, original, and full on state sovereignty is related to the conception of freedom inside at one under government regulation and the determination of the applicable law in all regions. At the same time the sovereignty of a state that borders the state sovereignty. In a country with sovereignty of other state, the company can do an agreement with the real, either in the form of bilateral or multilateral agreements. Being mentioned agreement legally binding for the states involved in the agreement. International agreement which would be legal resources by the obligation to carry out against countries involved. Proses assign mentioned two viewpoints in the position of the legal relationship between international law and national. One viewpoint is expecting the relationship between international law and national law as unity system and another viewpoint is seen as systems of the entities of two legal entities distinct and separate. Keywords: International Legal Status, System of National Legislation